SPE European Formation Damage Conference 1997
DOI: 10.2118/38170-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Field Validated Matrix Acidizing Simulator for Production Enhancement in Sandstone and Carbonates

Abstract: Although numerous sandstone and carbonate simulators have been developed during the past decade, few have been field validated. This paper addresses the field validation of a numerical simulator used for treatment design. Five matrix acidized wells were used for validation of the simulator. In most cases the simulator was within +10% of the actual skin reduction observed in the well. The simulator calculates the pressure at the formation face and within the multiple layers along the correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Formation damages caused by clay minerals (Illite, Kaolinite, Calcium montmorillonite and Sodium montmorillonite) easily occur in low permeability reservoirs. Although some conventional stimulations, such as hydraulic fracturing [17,18] and acidizing [19,20], are used to improve the flow conductivity of low permeability reservoirs, the stimulations may fail to acquire expected designation for geological complexity. Wettability of reservoir rock pore walls can be changed into hydrophobic by HLPN adsorption, which supplies a new approach to enhance water injection capacity of wells in low permeability reservoirs.…”
Section: Examples 1: Enhancing Water Injection Capacity Of a Well In mentioning
confidence: 99%
“…Formation damages caused by clay minerals (Illite, Kaolinite, Calcium montmorillonite and Sodium montmorillonite) easily occur in low permeability reservoirs. Although some conventional stimulations, such as hydraulic fracturing [17,18] and acidizing [19,20], are used to improve the flow conductivity of low permeability reservoirs, the stimulations may fail to acquire expected designation for geological complexity. Wettability of reservoir rock pore walls can be changed into hydrophobic by HLPN adsorption, which supplies a new approach to enhance water injection capacity of wells in low permeability reservoirs.…”
Section: Examples 1: Enhancing Water Injection Capacity Of a Well In mentioning
confidence: 99%
“…10,11 Emphasis was placed on horizontal wells. Horizontal Well With Thief Zone in the Middle Section (Zone 2).…”
Section: Chemical Diversion Systemsmentioning
confidence: 99%
“…22 Good treatment data including the acid concentration, pumping schedule, and surface pressure are required for evaluation of a simulator. Additionally, well information should include pre and post-treatment pressure falloff analyses, injection logs, porosity log, and formation mineralogy.…”
Section: Resultsmentioning
confidence: 99%
“…The commercial matrix simulator used in this study was developed as a "Joint Industry Project (JIP)" with input from several major operators. 22 Bartko et al 22 reported limited field validation results using the JIP simulator based on a model developed by Daccord et al. 15 The numerical simulator, calculates wormhole penetration into each radial grid block with time as a function of mineralogy, temperature, pump rate, acid type, etc.…”
Section: Acidizing Simulatormentioning
confidence: 99%